Sconed to death - Cahoon, Lynn (Cahoon, Lynn. Cat Latimer mystery., 2019)
Cat has a full plate at her Aspen Hills Warm Springs Resort, as a group of aspiring cozy mystery authors arrives for a writers retreat. So when baker Dee Dee Meyer stirs up trouble by filing a false complaint with the health inspector against the B&B<U+2014>all because she insists Cat's best friend Shauna stole her recipes<U+2014>Cat marches into the shop to confront her. But Dee Dee's about to have her own batch of trouble. Greyson Finn<U+2014>a celebrity chef and, until today, one of Denver's most eligible bachelors<U+2014>has been found dead in her bakery. Cat's uncle Pete, who happens to be the chief of police, warns her not to engage in any half-baked sleuthing. But as her curiosity rises, Cat's determined to discover who served the chef his just desserts<U+2014>before the killer takes a powder . . .